2012
DOI: 10.7150/jca.4584
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tumour Necrosis Factor-Alpha on Estrogen Metabolic Pathways in Breast Cancer Cells

Abstract: Tumor necrosis factor-alpha (TNF-α) is a proinflammatory cytokine that has been linked to breast cancer development. Estrogen metabolic pathway is also involved in breast carcinogenesis and DNA adducts formation. In this study we investigated the effect of TNF-α on the estrogen metabolic pathway in MCF-7, a breast cancer cell line. Capillary liquid chromatography/mass spectrometry (LC/MS) and High performance liquid chromatography (HPLC) were used for analysis of estrogen metabolites and estrogen-DNA adducts l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 51 publications
1
35
0
Order By: Relevance
“…Chronic exposure to lipopolysaccharide and other toxins shed by bacteria induces inflammation by activation of toll-like receptors in adipocytes, in turn releasing proinflammatory cytokines (35). In vitro exposure of breast epithelial cells to the proinflammatory cytokine TNF-␣ leads to increased total EM, 2-and 4-pathway metabolites, and the ratio of estradiol to estrone (36). Functional effects on estrogen-metabolizing enzymes induced by TNF-␣ include an increased expression of aromatase (CYP19), CYP1A1, and CYP1B1; reduced expression of catechol O-methyltransferase and nitroquinoxaline-01; and modulated expression of 17␤-hydroxysteroid dehydrogenase type I (36,37).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Chronic exposure to lipopolysaccharide and other toxins shed by bacteria induces inflammation by activation of toll-like receptors in adipocytes, in turn releasing proinflammatory cytokines (35). In vitro exposure of breast epithelial cells to the proinflammatory cytokine TNF-␣ leads to increased total EM, 2-and 4-pathway metabolites, and the ratio of estradiol to estrone (36). Functional effects on estrogen-metabolizing enzymes induced by TNF-␣ include an increased expression of aromatase (CYP19), CYP1A1, and CYP1B1; reduced expression of catechol O-methyltransferase and nitroquinoxaline-01; and modulated expression of 17␤-hydroxysteroid dehydrogenase type I (36,37).…”
Section: Discussionmentioning
confidence: 98%
“…In vitro exposure of breast epithelial cells to the proinflammatory cytokine TNF-␣ leads to increased total EM, 2-and 4-pathway metabolites, and the ratio of estradiol to estrone (36). Functional effects on estrogen-metabolizing enzymes induced by TNF-␣ include an increased expression of aromatase (CYP19), CYP1A1, and CYP1B1; reduced expression of catechol O-methyltransferase and nitroquinoxaline-01; and modulated expression of 17␤-hydroxysteroid dehydrogenase type I (36,37). Other in vivo studies have demonstrated that inflammation can drive estrogen production in the breast through the up-regulation of aromatase (38).…”
Section: Discussionmentioning
confidence: 99%
“…One-way ANOVA was used for all the quantifications: *P < 0.05, **P < 0.01. to 4-hydroxyestrogens, CYP1B1 is responsible for the activation of the invasive potential in human endometrial carcinomas [49]. Additionally, low-dose PTX also significantly and negatively influenced the expression of COMT, the major detoxifying enzyme for 4-hydroxyestrogens [39]. Collectively, we hypothesized that low-dose PTX can induce the dysregulated expression of estrogen metabolic enzymes and might provide a tumor-promoting microenvironment that facilitates the formation of metastases in liver.…”
Section: à4mentioning
confidence: 98%
“…7C). To the contrary, catechol-O-methyltransferase (COMT), the enzyme responsible for the detoxification of 4-OHE2 into methoxy derivatives [39], was obviously reduced in PTX-treated liver samples (Fig. 7D,E).…”
Section: Activation Of Nf-jb Is Required For the Oncological Behaviormentioning
confidence: 99%
“…Consequently, research on compounds that affect the estrogen metabolic pathway is ongoing. Example of these compounds are the dietary supplements resveratrol and N-acetylcysteine 8 and the tumor necrosis factor-alpha (TNF-α) 9 , as well as vegetable and carbohydrate consumption 10 . …”
Section: Introductionmentioning
confidence: 99%